Atrial ERK1/2 activation in the embryo leads to incomplete Septal closure: a novel mouse model of atrial Septal defect. Issue 1 (December 2017) - Yeh, Che-Chung; Fan, Yanying; Yang, Yi-Lin; Mann, Michael
Abstract Background MEK1 mutation and activated MAPK signaling has been found in patients with RASopathies and abnormal cardiac development. Previous studies have suggested that regulation of fetal MAPK signaling is essential for normal cardiac development. We investigated the effect of active MEK1 overexpression on fetal atrial septal development. Methods and results An inducible double transgenic (DTg) mouse model was developed in which cardiac-specific fetal expression of a constitutively active form of human MEK1 (aMEK1) was induced primarily in the atrium via the withdrawal of doxycycline from the drinking water of pregnant mice. Atrial septal defect (ASD) was found in 51% (23/45) of DTg mice. Fifty-two percent (12/23) of ASD mice died before weaning, and surviving ASD mice exhibited hypertrophic hearts with enlarged right atria and decreased fractional shorting (40 ± 2% vs. 48 ± 0%, p  < 0.05). The model mimicked human ASD in several key clinical features: severe ASD was associated with growth impairment; ASD-specific mortality was highest within the early postnatal period; despite an even distribution of ASD among the sexes, early mortality was significantly higher in males. The expression of aMEK1 and increased phosphorylation of ERK1/2 was documented via Western blot in DTg fetal hearts, with the largest increases seen in atrial tissue. In an alternative transgenic aMEK1 model with elevated atrial MKP3 expression and corresponding suppression of increases in ERK1/2 phosphorylation, animals did not develop ASD. Conclusion This new model of ASD suggests that enhanced atrial MEK1-ERK1/2 signaling during fetal development disrupts normal atrial septation, possibly regulated by the balance of ERK1/2 phosphorylation.